2012
DOI: 10.1111/j.1758-5872.2012.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression in the elderly: A review and update

Abstract: Depression is a major source of suffering and disability among the elderly. It may be overlooked among elders because of its co-occurrence with the aging process, grief, dementia, and medical illness. The author reviewed the field in 1994, and in this paper describes important developments of the past two decades. These include evolving concepts in diagnosis such as minor depression, vascular depression, and the depression of Alzheimer's disease. Complex inter-relationships among depression and medical disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 54 publications
2
21
0
2
Order By: Relevance
“…Supporting previous research, the influential role of depression in the model indicates the importance of early diagnosis and adequate treatment of depressive symptoms among older adults (Casey, 2012;Moussavi et al, 2007). Similarly, the role of self-efficacy in the model highlights the importance of enhancing perceptions of competence among older adults (Clark & Dodge, 1999;Grembowski et al, 1993), particularly given that self-efficacy beliefs are more likely to diminish with age (Esposito, Gendolla, & Van der Linden, 2014).…”
Section: Discussionsupporting
confidence: 66%
“…Supporting previous research, the influential role of depression in the model indicates the importance of early diagnosis and adequate treatment of depressive symptoms among older adults (Casey, 2012;Moussavi et al, 2007). Similarly, the role of self-efficacy in the model highlights the importance of enhancing perceptions of competence among older adults (Clark & Dodge, 1999;Grembowski et al, 1993), particularly given that self-efficacy beliefs are more likely to diminish with age (Esposito, Gendolla, & Van der Linden, 2014).…”
Section: Discussionsupporting
confidence: 66%
“…3 Research on depression demonstrates that it is a major cause of emotional distress in older age and a factor potentially contributing to the pathogenesis of a variety of diseases. 15,16 Depressed elderly patients often experience a deterioration of their daily functioning and quality of life (QoL), as well as low moods. 17 Additionally, the recent reports show that both depressive and anxiety symptoms are important for effective therapeutic process in patients with AF.…”
Section: Introductionmentioning
confidence: 99%
“…Depression has been a significant mental issue among the elderly around the world [ 1 3 ]; this mental condition usually causes poor health, emotional suffering, family disruption, mortality, and increased medical care costs [ 4 6 ]. A meta-analysis concluded that among the elderly with depression symptoms, only 33% remained healthy after two years, 33% became clinically depressed, and 21% died [ 7 ].…”
Section: Introductionmentioning
confidence: 99%